2007
DOI: 10.1253/circj.71.100
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of S-Glutathionylated Proteins as a Risk-Marker for Arteriosclerosis Obliterans

Abstract: Background Oxidative stress plays a role in the development of chronic peripheral arterial disease (PAD) because under these conditions redox regulation is impaired, inducing the S-glutathionylation of proteins. A method of estimating the levels of S-glutathionylated proteins has been developed using biotinylated glutathione S-transferase, which allows the study of their crucial role in the oxidative stress-related progression of PAD. Methods and ResultsThe serum levels of S-glutathionylated proteins were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…Steady state levels of Grx itself appear to be dynamically regulated, and increases in Grx occur in cancer and cardiovascular disease [83,103]. Elevated levels of Sglutathionylated proteins in serum have been suggested to represent a risk-marker for arteriosclerosis obliterans [104]. Recent studies from our laboratory (Y J-H) have demonstrated that multiple stimuli, such as the TLR ligands, lipopolysaccharide (LPS) and CpG DNA, interleukin-4, and transforming growth factor-beta 1 (TGF-β1) result in decreases in Grx activity in primary lung epithelial cells, in association with decreases in Grx1 mRNA, in response to TGF-β1 [105].…”
Section: Biochemical and Genetic Regulation Of Reversible Cysteine Oxmentioning
confidence: 99%
“…Steady state levels of Grx itself appear to be dynamically regulated, and increases in Grx occur in cancer and cardiovascular disease [83,103]. Elevated levels of Sglutathionylated proteins in serum have been suggested to represent a risk-marker for arteriosclerosis obliterans [104]. Recent studies from our laboratory (Y J-H) have demonstrated that multiple stimuli, such as the TLR ligands, lipopolysaccharide (LPS) and CpG DNA, interleukin-4, and transforming growth factor-beta 1 (TGF-β1) result in decreases in Grx activity in primary lung epithelial cells, in association with decreases in Grx1 mRNA, in response to TGF-β1 [105].…”
Section: Biochemical and Genetic Regulation Of Reversible Cysteine Oxmentioning
confidence: 99%
“…We examined levels of S-glutathionylated serum proteins and found an increase in patients with ASO ( Fig. 3) 50) . The data suggest that oxidative stress and a balance of redox regulation play a role in vascular function.…”
Section: Role Of Grx In Serummentioning
confidence: 99%
“…This antibody also reacted with multiple S-glutathionylated proteins in serum from a CS patient (lane 2) and a patient with arteriosclerosis obliterans who were found to have an increase of serum S-glutathionylated proteins in our previous study [21] (lane 3, the left image in Figure 1B).…”
Section: Serum Levels Of S-glutathionylated Proteins Increased In Cs mentioning
confidence: 56%
“…In another study, the S-glutathionylated proteins in serum were found to differ between CS patients and patients with arteriosclerosis obliterans [21]. It will be interesting to determine whether the pattern of S-glutathionylated proteins in serum has disease specificity.…”
Section: Altered Levels Of S-glutathionylated Proteins Have Been Recementioning
confidence: 95%